Evaluation of Articulated CAT 745 Fuel Ratio Based on Haul Road Geometry at PT Hillconjaya Sakti Site PT Adhi Kartiko Pratama Tbk - Aryanti Virtanti Anas; Wahyuni S; Rini Novrianti Sutardjo Tui; Rizki Amalia (EPI International Journal of Engineering, 2025)
The distance for transporting overburden at PT Hillconjaya Sakti reaches hundreds of meters. Based on actual conditions, Articulated CAT 745 queues often occur on certain haul road segments due to unsuitable haul road conditions so the fuel ratio value is in the low performance category. The purpose of this study is to evaluate the fuel ratio value and provide recommendations for improving the geometry of haul roads to meet the established fuel ratio value standards. Multiple linear regression analysis using Eviews 12 VS was used to determine the variables that significantly affect the fuel consumption of hauler based on haul road geometry. Road grade, total resistance, travel time and speed of the hauler are independent variables, while fuel consumption is the dependent variable. Based on the results of data processing, a fuel ratio value of 1.85 was obtained and the parameters that had a significant effect on fuel consumption were total resistance and travel time. Improvement of haul road conditions based on ESDM Decree No. 1827 K/30/MEM/2018 and AASHTO Manual Rural High Way Design. The fuel ratio value after repairs decreased to 0.60 and was in the best performance category based on PT Hillconjaya Sakti's standard fuel ratio value.